Daluyong manggagawang Pilipino sa panahon ng globalisasyon - Ilagan, Bonifacio 1951-; LC Purchase Collection (Library of Congress) (Manila, Philippines IBON Foundation, Video Production Unit, 2001)
Documentary captures the impact of globalization on workers in the Philippines. No job security, union busting, violation of workers' rights and welfare are the lament of workers in the country who have been hit by globalization. They show that the way to fight globalization is through militant struggle.
Summary from container.
Not viewed.
Also issued in Videocassette format.
LC Purchase Collection.
In Tagalog interspersed with English.
Keywords: Globalization -- Philippines; Documentary